Efficiency of Different Electrolytes on Electrochemical Chloride Extraction to Recover Concrete Structures under Chloride-Induced Corrosion - Thamara Tofeti Lima; Ki Yong Ann (Advances in Materials Science and Engineering)
Chloride-induced corrosion is one of the main causes of concrete deterioration and imposes a challenge to sustainability. Traditional techniques to repair corroded structures consisted of basically removing the damaged area, which was either economical or sustainable. Therefore, electrochemical chloride extraction (ECE) gained popularity for being an efficient nondestructive treatment applied temporarily to structures. On this line, this manuscript aims to raise the efficiency of ECE by an optimal decision of the treatment setup concerning the electrolyte choice. Three different electrolytes were tested, namely, tap water, calcium hydroxide, and lithium borate. Experimental results pointed to lithium borate as the most efficient electrolyte for extracting chlorides while calcium hydroxide was a better choice to repassivate the structure and even heal cracks, due to a possible electrodeposition of the electrolyte ions on the cement matrix. Thus, depending on the main goal of the treatment, different electrolytes achieve a better performance, which highlights the importance of pretreatment evaluation to see in which stage of corrosion damage is the structure.